Resourcefulness narratives: Transforming actions into stories to mobilize support - Fisher, Greg; Neubert, Emily; Burnell, Devin (Journal of Business Venturing, 2021)
Entrepreneurs regularly confront resource constraints as they attempt to bring their ideas to fruition. To overcome resource constraints, they often try to mobilize resources from external resource providers and use narratives as a critical tool to do so. We theorize that a particular type of narrative – a resourcefulness narrative – will significantly impact an entrepreneur's ability to mobilize support from resource providers. A resourcefulness narrative is a discursive, temporal account of past or ongoing entrepreneurial actions, whereby an entrepreneur is presented as using, assembling, or deploying resources in creative ways in order to overcome an impediment. We argue that a resourcefulness narrative generates positive emotional and cognitive reactions from external resource providers such that they are inclined to support a venture. Furthermore, these effects are contingent on the general level of resource scarcity or munificence in a venture's environment, the level of uncertainty underpinning the venture, the entrepreneur's experience, and the recency of the actions described within the narrative. By acting resourcefully and transforming that action into a narrative, entrepreneurs can resourcefully mobilize support.